Chronic Thalidomide and Chemoembolization for Hepatocellular Carcinoma. (31st October 2014) - Wu, Jennifer; Ng, Jennifer; Christos, Paul J.; Goldenberg, Alec S.; Sparano, Joseph; Sung, Max W.; Hochster, Howard S.; Muggia, Franco M.
Abstract : Background: Transcatheter arterial chemoembolization (TACE) has been used to curtail tumor vasculature and delay tumor progression in hepatocellular carcinoma (HCC). We conducted a phase I trial to evaluate the efficacy and toxicity of thalidomide when combined with TACE in patients with advanced HCC. Methods: Between June 2000 and November 2003, 56 patients with unresectable HCC and amenable to TACE were enrolled. The starting dose of thalidomide was 200 mg/day and was escalated every 2 weeks as tolerated to a maximum dose of 1, 000 mg/day. Dose reductions and discontinuation were determined by toxicity. TACE was performed 4 weeks after initiation of thalidomide therapy and repeated as necessary. Results: Overall, 47 and 55 patients were evaluable for response and toxicity, respectively; the median dose of thalidomide given was 200 mg/day. Three patients (6.38%) patients achieved complete responses, whereas 10 (21.3%) had partial responses, for an overall response rate of 27.7%, and 27 (57.5%) had stable disease. Median progression‐free survival was 7 months (95% confidence interval [CI]: 5–10 months), and median OS was 21 months (95% CI: 16–28 months) (Fig. 1 ). Fatigue and lethargy (49.1%), constipation (47.3%), and nausea (43.6%) were common. Grade 3–4 toxicities consisted mostly of increased aspartate aminotransferase (43.6%) and elevated alanine aminotransferase (38.2%) (Table 1 ). Conclusion: Thalidomide and TACE were commonly associated with nonhematologic side effects, with fatigue and constipation being prominent. With a lack of clear therapeutic benefit, this combination is unlikely to be pursued for HCC. Abstract : 摘要 背景 . 经导管肝动脉化疗栓塞术（TACE）在肝细胞癌（HCC）的治疗中用于减少肿瘤血供和延缓肿瘤进展。我们开展了一项 I 期试验，旨在评价沙利度胺联合 TACE 在进展期 HCC 患者中的有效性和毒性。 方法 . 2000 年 6 月∼ 2003 年 11 月，共入组 56 例不可手术切除且适于行 TACE 的 HCC 患者。沙利度胺的起始剂量为 200 mg/天，视耐受情况每 2 周上调一次剂量，直至最大剂量 1000 mg/天。根据毒性决定下调给药剂量和停药。TACE 于开始沙利度胺治疗 4 周后实施，并且按需重复实施。 结果 . 总体而言，47 例患者可评估治疗反应，55 例可评估毒性；中位沙利度胺剂量为 200 mg/天。3 例患者（6.38%）达到完全缓解，10 例（21.3%）达到部分缓解，总缓解率为 27.7%。27 例患者（57.5%）疾病稳定。中位无进展生存为 7 个月[95% 可信区间（CI）：5 ∼ 10 个月]，中位总生存（OS）为 21 个月（95%CI：16 ∼ 28 个月）（图 1）。疲乏及嗜睡（49.1%）、便秘（47.3%）和恶心（43.6%）较为常见。3/4 级毒性事件主要包括天门冬氨酸氨基转移酶水平升高（43.6%）和丙氨酸氨基转移酶水平升高（38.2%）（表 1）。 结论 . 沙利度胺和 TACE 多与非血液学不良事件相关，主要是疲乏和便秘。由于缺乏明显的治疗获益，这一联合方案不太推荐用于 HCC 治疗。 The Oncologist 2014;19:1229–1230